Enhancing Learners' Autonomy in Vocabulary Learning in EFL Libyan Classroom - Noura Winis Ibrahim; Yusuf H. Alhodairy (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the most challenging issues that EFL learners encounter is vocabulary learning. Teaching methodologies, nowadays, take into consideration learner autonomy compared to the past that depends totally on instructors. The aim of the study is to address the importance of learning autonomy in teaching English as a foreign language (EFL) in Libyan context as teachers can facilitate learning process by demonstrating certain strategies where necessary. This study also focuses on exploring how students experience out-of-class autonomous vocabulary learning. A questionnaire and interview were used in this study. The questionnaire is meant for the students and the interview is for teachers. The participants of the study were 15 students and 5 teachers. The findings reveal that learners are eager to be enhanced to learn vocabulary autonomously and need to be guided by their teachers using effective strategies. It is very important to apply autonomous learning to develop vocabulary knowledge as students lack lexical competence.